Polymorphisms in the MTHFR and MTR genes and the risk of varicose veins in ethnical Russians - Shadrina, Alexandra Sergeevna; Sevost'ianova, Kseniya Sergeevna; Shevela, Andrey Ivanovich; Soldatsky, Evgenii Yurievich; Seliverstov, Evgenii Igorevich; Demekhova, Marina Yurievna; Shonov, Oleg Aleksandrovich; Ilyukhin, Evgenii Arkadievich; Smetanina, Mariya Aleksandrovna; Voronina, Elena Nikolaevna; Pikalov, Ilya Victorovich; Zolotukhin, Igor Anatolyevich; et al. (Biomarkers, 2016)
Objectives: The objective of this study was to study the association of polymorphisms MTHFR C677T (rs1801133) and MTR A2756G (rs1805087) with the risk of varicose veins in ethnical Russians. Methods: We genotyped 475 patients with varicose veins, 168 individual without chronic venous disease, and the population-based group of 896 subjects. Association was studied using logistic regression analysis adopting co-dominant, additive, recessive, and dominant models of inheritance. Results: None of the polymorphisms showed a statistically significant association with the risk of varicose veins. Conclusions: Our results provide evidence that the studied polymorphisms do not contribute to genetic susceptibility to varicose veins in ethnical Russians.